Leksikaliseringsmønstre ved verber. Et komparativt-typologisk studie - Durst-Andersen, Per (HERMES - Journal of Language and Communication in Business, 2005)
This paper combines two thematic areas which have been in the focus of linguists’ interest for some years, viz. studies in lexicalization patterns of verbs and grammaticalization studies. Instead of comparing lexicalization patterns of different lan guages I have chosen to compare various stages of the same language, namely Old Russian and Modern Russian. This enables me to analyze the interrelationship between lexicalization patterns and grammatical categories. The paper argues that it is important to distinguish between naming principle and lexicalization pattern. A language may describe an image or an idea and therefore has to make a semiotic choice between these two different naming principles. Having chosen a speciﬁc naming principle a language has to determine which parts of the image or which parts of the idea it wants to focus on or specify. My analysis shows that the Old Russian verb describes the idea, i.e. the ground-propositional structure, whereas the Modern Russian verb describes the image, i.e. the ground-situational structure. Moreover, it appears that Old Russian focuses on the state description without paying attention to the activity description, while Modern Russian takes into account both the state situation and the activity situation, but with the main focus on the former – the latter is only treated in prototypical terms. The shift in naming strategy and lexicalization pattern from Old Russian to Modern Russian can only be explained by the introduction of the new category of aspect, a determinant category in Modern Russian.